Fibroblasts Advances in Inflammation, Autoimmunity and Cancer - Frank Bertoncelj, Mojca; Lakota, Katja (Biochemistry, 2021)
Fibroblasts - Advances in Inflammation, Autoimmunity and Cancer presents recent advances in understanding the roles of fibroblasts and mesenchymal stem cells in tissue homeostasis and the development of human disease. The book delves into general principles of fibroblast and mesenchymal stem cell biology and their diversity across the human body. It highlights these cells' unique and shared characteristics across organs (e.g., vasculature, kidney, joints and exocrine glands) and specific pathologies (e.g., tissue damage, inflammation, fibrosis and cancer). A particular focus is set on the roles of fibroblasts in disease chronicity, recurrence, progression, therapeutic resistance and utilisation of the advancing knowledge for developing new therapeutic approaches within and beyond disease boundaries.